DWT 2021
DOI: 10.5004/dwt.2021.27887
|View full text |Cite
|
Sign up to set email alerts
|

Performance studies of indigo dye removal using TiO2 modified clay and zeolite ultrafiltration membrane hybrid system

Abstract: Dyes contamination causes serious damages to the aquatic life's and human health.With increase in these persistent organic contaminants accumulation around the world, performant environmentally friendly and low cost materials and techniques are required to protect ecosystem and human. In this study, the efficacy of titania-smectite nanocomposites (Sm-TiO2 NCs) at removing indigo blue (IB) dye was assessed by both batch adsorption and hybrid treatment combining adsorption and ultrafiltration (UF) processes. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The application of this nanocomposite for the removal of Cr(VI) from industrial wastewater showed an adsorption capacity of chromium of 22.3 mg/g at the pH range 3.8-5.5. The removal kinetics was found to follow the Freundlich Pseudo-first-order [24] pseudo-second-order and the maximum amount adsorbed was best simulated by the Langmuir isotherm model [42].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The application of this nanocomposite for the removal of Cr(VI) from industrial wastewater showed an adsorption capacity of chromium of 22.3 mg/g at the pH range 3.8-5.5. The removal kinetics was found to follow the Freundlich Pseudo-first-order [24] pseudo-second-order and the maximum amount adsorbed was best simulated by the Langmuir isotherm model [42].…”
Section: Discussionmentioning
confidence: 96%
“…Thermodynamic properties, such as enthalpy, entropy and the free energy were also estimated to provide insight into the adsorption mechanism during the adsorption removal of the chromium. These NP are used in different applications such as membrane separation [15,[21][22][23], hybrid system and adsorption [24] to treat different effluents. High performances of these NP encourage their use in the elimination of heavy metals by adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…(7) The sample loading flow rate (1, 2, 3, 4, 5, and 6 ml/min). (8) The volume of desorption solvent (1, 2, 3, 5, 7, and 9 ml). The food samples including pork and fish used in the experiments were purchased from supermarkets near the laboratory (Luzhou, Sichuan).…”
Section: Optimization Of the Parameters Of Spementioning
confidence: 99%
“…Even very small amounts of dyes can reduce light transport in the water environment and thus reduce plant photosynthesis. More seriously, these dye wastewaters can lead to contamination of water, thus causing tumors, mutations and heart diseases to human (Basu & Kumar, 2015;Romdhani, et al, 2021;Salleh, Mahmoud, Karim, & Idris, 2011). For food, food dyes are found in many foods, such as meat, cereals, confectionery, beverages, and are even applied in pharmaceutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation